The effect of COVID‑19 restrictions on sleep quality of university students and variables predicting sleep quality - Bulut, Arzu; Şengül, Halil; Demir Uslu, Yeter; Baş, Kazım; Tosun, Nurperihan; Şengül, Halil (Wolters Kluwer - Medknow, 2022)
BACKGROUND/AIM: The COVID‑19 pandemic has created a long period of stress for people worldwide and has significantly affected sleep duration. The pandemic revealed new stress factors that are likely to affect sleep. Uncertainty is a factor that leads to anxiety and depression, which affects sleep. It should also be noted that reductions in sleep quality rather than sleep duration are associated with negative consequences on mental health. This study aims to investigate online that how this situation affected university students. MATERIALS AND METHODS: This research, with a descriptive study design, was conducted in Turkey between June 01, 2021 and July 30, 2021. The sample included 604 people who accepted voluntary participation, chosen by the random selection method. In the study, sociodemographic information form, Pittsburgh sleep quality index (PSQI), morningness–eveningness questionnaire scale (MEQ Scale), Beck depression inventory (BDI), and Beck anxiety inventory (BAI) were used as data collection tools. Pearson correlation analysis was utilized to examine the relationship between the scales. Multiple regression analysis was performed to investigate the role of morningness– eveningness, anxiety, depression, and insomnia severity on sleep quality. RESULTS: Sleep quality was negatively correlated with morningness–eveningness scores (r = –0.32, P < 0.01), and positively and significantly related with anxiety (r = 0.43, P < 0.01), depression (r = 0.40, P < 0.01) and insomnia severity (r = 0.55, P < 0.01). According to regression coefficients, while anxiety (ꞵ = 0.041, P < 0.001) and insomnia severity scores (ꞵ = 0.226, P < 0.001) positively predicted sleep quality, depression did not predict it significantly (ꞵ = 0.009, P > 0.05). A significant difference was found in sleep quality according to morning, evening, and intermediate types (F = 27.401, P < 0.001). CONCLUSION: Events related to the COVID‑19 pandemic are associated with reduced sleep quality in connection with increasing negative moods. Considering the importance of sleep for a healthy life, efforts should be made to raise awareness about this issue and to provide psychological help to affected individuals.
Keywords: Anxiety; COVID‑19 pandemic; Depression; Morningness‑eveningness; Sleep quality; University students